The effect of brisk walking exercise on immune function, intestinal fatty acid binding protein, fatigue and severity scores in patients with irritable bowel syndrome : a randomised controlled trial - Rooshdi, Raja Abdul Wafy Raja Muhammad (2020)
Background: Irritable bowel syndrome (IBS) is the most prevalent functional gastrointestinal disorder, which is challenging to treat as no specific treatment are available. It has been shown that fatigability increases in physically active IBS patients; it is associated with the pro-inflammatory process, which takes place in the muscles. Physical activity has proven to increase the anti-inflammatory process and maybe a potential in IBS treatment. Method: This is a randomized controlled intervention study, involving IBS subjects of more than 18 years old and less than 70 years old whom meet the ROME III criteria were recruited between June 2019 till August 2019 from Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. Subjects subsequently assigned into two groups, control and exercise groups where the exercise group underwent moderate intensity exercises for four weeks. Measurements were taken twice, which is before and after the completion of the four-week intervention period. Results: A total of 44 participants were analyzed. There was a significant difference between two randomization factors in IL-6 between exercise group compared with control group among IBS patients (P < 0.001; 95% CI 14.70 – 27.80). There was no significant difference observed among two groups for TNF-α (P = 0.274; 95% CI - 20.57 – 70.61) as well as intestinal cell damage markers (iFABP) (P = 0.288; 95% CI -71.04 – 21.65). In the IBS-SSS comparison, there was no significant difference noted between two randomization factors (P=0.157; 95% CI -6.09 – 36.37). Similarly, no Background: Irritable bowel syndrome (IBS) is the most prevalent functional gastrointestinal disorder, which is challenging to treat as no specific treatment are available. It has been shown that fatigability increases in physically active IBS patients; it is associated with the pro-inflammatory process, which takes place in the muscles. Physical activity has proven to increase the anti-inflammatory process and maybe a potential in IBS treatment. Method: This is a randomized controlled intervention study, involving IBS subjects of more than 18 years old and less than 70 years old whom meet the ROME III criteria were recruited between June 2019 till August 2019 from Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. Subjects subsequently assigned into two groups, control and exercise groups where the exercise group underwent moderate intensity exercises for four weeks. Measurements were taken twice, which is before and after the completion of the four-week intervention period. Results: A total of 44 participants were analyzed. There was a significant difference between two randomization factors in IL-6 between exercise group compared with control group among IBS patients (P < 0.001; 95% CI 14.70 – 27.80). There was no significant difference observed among two groups for TNF-α (P = 0.274; 95% CI - 20.57 – 70.61) as well as intestinal cell damage markers (iFABP) (P = 0.288; 95% CI -71.04 – 21.65). In the IBS-SSS comparison, there was no significant difference noted between two randomization factors (P=0.157; 95% CI -6.09 – 36.37). Similarly, no significant difference was found with regards to fatiguability using MFSI-SF score among two groups (P=0.212; 95% CI -1.46 – 6.41). Conclusion: Inflammatory markers such as IL-6, TNF-α, and iFABP have some role in determining cellular inflammation and injury. Still, there is a lack of accuracy in terms of the evidence showing that physical activity has some role in reducing these inflammatory markers. No significant difference was demonstrated in fatigability between the exercise and control groups among IBS patients.